STATUS DESA PESISIR UNTUK PENGEMBANGAN INDUSTRI PERIKANAN TERPADU DI KOTA AMBON - M. J. Papilay; M. Fedi A. Sondita; Daniel R. Monintja; Victor Nikijuluw (Institut Pertanian Bogor, 2012)
Ambon City is located in coastal area of Ambon island. Economic contributon of fisheries sector to its PDRB was relativey high (about 15%) but the poverty level of itspopulation is high. Since coastal villages are the main players of the fisheries sector, its development approach to promote community welfare should be based on the characteristicsof the 32 coastal villages. This study was designed to develop a methodology for determining coastal village status in promoting integrated fisheries industry in Ambon City. This study uses 17 indicators representing three main variables comprising fisheries business, fisheries infrastructure and socio-cultural aspects of coastal communities. Based on score calculation, there are three categories of coastal villages, i.e. desa mina mula (TSS < 1,5), mina mandiri (1,5≤ TSS ≤ 2,39), and mina politan (TSS > 2,39). The analysis concludes no village of mina politan, 30 villages of mina mandiri, and 2 villages of mina mula. Such diverse characteristics indicate that fisheries development approach should vary among villages to ensure development effectiveness.Kata kunci: coastal communities, fisheries development status, mina politan